2020
DOI: 10.1007/s41669-020-00202-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Sequential Biologic Therapy with Ixekizumab Versus Secukinumab in the Treatment of Active Psoriatic Arthritis with Concomitant Moderate-to-Severe Psoriasis in the UK

Abstract: Background Interleukin-17A (IL-17A) antagonists are a recent innovation for treating psoriatic arthritis (PsA). There are currently no cost-effectiveness analyses (CEAs) comparing the IL-17A antagonists ixekizumab and secukinumab in PsA from a UK perspective. Objective We conducted a CEA from the UK National Health Service perspective to compare ixekizumab versus secukinumab in patients with PsA and concomitant moderate-to-severe plaque psoriasis. Methods A Markov model was developed based on the widely accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…IL-17A is an ideal drug target because of its broad involvement in many host defense mechanisms by inducing proinflammatory cytokines and chemokines that participate in neutrophil and macrophage recruitment to the site of injury (17). Indeed, recent reports have shown that IL-17A plays a role in skin wound healing (18) and gut epithelial repair (19) while aIL-17A and aIFNg mAbs have been developed to treat psoriasis (20) and lymphohistiocytosis (21), respectively, in humans, with favorable outcomes. IL-17A and IFNg are therefore ideal targets for the future development of therapeutic antibodies to test using the pig biomedical model, to affirm the cytokine's involvement in many host-defense mechanisms (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A is an ideal drug target because of its broad involvement in many host defense mechanisms by inducing proinflammatory cytokines and chemokines that participate in neutrophil and macrophage recruitment to the site of injury (17). Indeed, recent reports have shown that IL-17A plays a role in skin wound healing (18) and gut epithelial repair (19) while aIL-17A and aIFNg mAbs have been developed to treat psoriasis (20) and lymphohistiocytosis (21), respectively, in humans, with favorable outcomes. IL-17A and IFNg are therefore ideal targets for the future development of therapeutic antibodies to test using the pig biomedical model, to affirm the cytokine's involvement in many host-defense mechanisms (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Real-world disease-specific data sources can provide essential follow-up data on entire treatment sequences, and potentially be used to emulate a pragmatic randomised trial of dynamic treatment sequences [27,[163][164][165]. If these data sources are going to be useful, treatment sequences need to be considered during the planning and development stages.…”
Section: Simplifying Assumptions Taxonomymentioning
confidence: 99%